The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.minpro.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of methyl cyclohexanemethanol and methyl isobutyl carbinol as frother for coal flotation

Abstract: Methyl isobutyl carbinol (MIBC), an aliphatic alcohol, is widely used as a frothing reagent in coal flotation but it has safety concerns owing to its low flash point (approximately 40 °C). In the present work, we studied a cyclic alcohol, methyl cyclohexanemethanol (MCHM) with a high flash point (approximately 110 °C) and compared its coal flotation performance with that of MIBC. A bottom-driven mechanical flotation cell and two coking coals of distinct floatability, namely A and B, were used. Collectorless fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The surface active agent methyl isobutyl carbinol (MIBC) (4-methyl-2-pentanol) is used as an example since it is commonly used in mineral processing to control the size distribution of bubbles. [111,112] Fig. 13 shows the surface tension of MIBC for a large range of concentrations from the data from Bournival et al [35,89].…”
Section: Interfacial Instabilitymentioning
confidence: 99%
“…The surface active agent methyl isobutyl carbinol (MIBC) (4-methyl-2-pentanol) is used as an example since it is commonly used in mineral processing to control the size distribution of bubbles. [111,112] Fig. 13 shows the surface tension of MIBC for a large range of concentrations from the data from Bournival et al [35,89].…”
Section: Interfacial Instabilitymentioning
confidence: 99%
“…Many authors have investigated the influence of surfactant type and concentration on the flotation performance (e.g., [7,9,[31][32][33][34][35][36][37][38][39][40][41]). An example involving coal flotation is shown in Figure 16.…”
Section: Influence Of Frother Characterization Parameters On Flotationmentioning
confidence: 99%
“…Other authors studied the effect of methyl cyclohexane methanol and cyclic frothers, as well as comparing coal flotation performance with methyl isobutyl carbinol using two coking coals with different floatability. The results showed that it was an effective alternative to methyl isobutyl carbinol (Hangil et al, 2016).…”
Section: Introductionmentioning
confidence: 99%